INTRODUCING YOUNGER PUPILS TO TERMS AND PROFESSIONALISMS (Texas Journal of Multidisciplinary Studies, 2022)
In this article were discussed the study of terms and professionalisms in Uzbek linguistics, some of the terms found in primary school textbooks, and methods of communicating them to pupils.